2021
DOI: 10.3390/ijerph18168508
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Sedentary Time with Heart Rate and Heart Rate Variability in Adults: A Systematic Review and Meta-Analysis of Observational Studies

Abstract: Purpose: To evaluate if sedentary time (ST) is associated with heart rate (HR) and variability (HRV) in adults. Methods: We systematically searched PubMed and Google Scholar through June 2020. Inclusion criteria were observational design, humans, adults, English language, ST as the exposure, resting HR/HRV as the outcome, and (meta-analysis only) availability of the quantitative association with variability. After qualitative synthesis, meta-analysis used inverse variance heterogeneity models to estimate poole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 68 publications
1
15
0
Order By: Relevance
“…We recently published a systematic review and meta-analysis that found negligible and clinically trivial correlations between SB and HR with no significant association of SB with HRV 16 . However, the limitations of the existing studies were notable and included not using thigh-mounted monitors to measure SB, not accounting for MVPA in several studies, and not differentiating between occupational versus nonoccupational SB 16 . Our findings address these limitations and report significant and paradoxical associations of occupational and nonoccupational SB with resting and nocturnal ambulatory HR and resting HRV.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We recently published a systematic review and meta-analysis that found negligible and clinically trivial correlations between SB and HR with no significant association of SB with HRV 16 . However, the limitations of the existing studies were notable and included not using thigh-mounted monitors to measure SB, not accounting for MVPA in several studies, and not differentiating between occupational versus nonoccupational SB 16 . Our findings address these limitations and report significant and paradoxical associations of occupational and nonoccupational SB with resting and nocturnal ambulatory HR and resting HRV.…”
Section: Discussionmentioning
confidence: 99%
“…16 However, the limitations of the existing studies were notable and included not using thigh-mounted monitors to measure SB, not accounting for MVPA in several studies, and not differentiating between occupational versus nonoccupational SB. 16 Our findings address these limitations and report significant and paradoxical associations of occupational and nonoccupational SB with resting and nocturnal ambulatory HR and resting HRV. Higher nonoccupational SB was associated with slightly higher resting and nocturnal ambulatory HR, whereas higher occupational SB was associated with slightly lower nocturnal ambulatory HR.…”
Section: Associations Of Sb With Resting and Nocturnal Ambulatory Hr ...mentioning
confidence: 99%
See 1 more Smart Citation
“… 3 The regularisation of CAF through improved physical activity (PA) and cardiorespiratory fitness (CRF) has been observed and reported among physically active, normal-weight individuals. 8 , 9 , 10 , 11 Sedentary lifestyle predominates among overweight and obese individuals and contributes largely to cardiac autonomic dysfunction. 9 Interestingly, a 10% weight gain over initial body weight was reported to decrease parasympathetic tone and increase sympathetic tone among a group of non-obese individuals.…”
Section: Introductionmentioning
confidence: 99%
“… 8 , 9 , 10 , 11 Sedentary lifestyle predominates among overweight and obese individuals and contributes largely to cardiac autonomic dysfunction. 9 Interestingly, a 10% weight gain over initial body weight was reported to decrease parasympathetic tone and increase sympathetic tone among a group of non-obese individuals. 12 , 13 The evidence on how increasing adiposity may affect CAF among overweight and obese individuals is worth exploring.…”
Section: Introductionmentioning
confidence: 99%